Application of Vertical Flow Constructed Wetland for Organic Pollutant Removal from Petroleum Refinery Wastewater - Lestari, Amelia Eka; Widiasa, I Nyoman (Reaktor, 2024)
This study examined the application of a pilot-scale Vertical Flow Constructed Wetland (VFCW) system for secondary oil refinery effluent treatment at PPSDM MIGAS, Indonesia. The VFCW technique, known for its simplicity, minimal operational cost, and environmental friendliness, was used to reduce organic pollutants (BOD and COD) to meet the standards and minimize pollutant levels. The system, constructed with a closed pond including gravel and sand substrates, and planted with Typha angustifolia, was evaluated under Hydraulic Retention Times (HRT) of 3, 4, and 5 days. The results showed BOD removal efficiencies of 52.9%, 54.4%, and 53.6%, and COD removal efficiencies of 35.7%, 49.1%, and 47.2% for hydraulic retention times of 3, 4, and 5 days, respectively. Statistical investigation (ANOVA) showed no significant difference (P > 0.05) in BOD removal efficiencies across HRTs and COD removal for 4 and 5 days. These findings implied diminishing benefits after 4 days for organic matter removal operations. The limited BOD and COD removal, in contrast to other investigations, was due to the short acclimatization time (7 days) for the Typha angustifolia to drive oxygen sufficiency and biofilm formation. These findings underlined the capability of the VFCW system to reduce wastewater contaminants sustainably and economically in tropical areas such as Indonesia. A 4-day HRT is recommended for practical applications in refinery wastewater treatment with pollutant loads up to complement. Extended acclimatization duration and improved operational settings are recommended to enhance the performance of the VFCW. This study illustrates the feasibility of VFCW as a scalable and environmentally sustainable solution for wastewater control in the petroleum industry sector. Keywords: VFCW, organic pollutants, retention time, removal efficiency, acclimatization.